The four Ds deconstructed - Renee Bittoun (Elsevier, 2003)
Abstract For decades, pamphlets provided by credible government authorities have reproduced tips for quitting smoking, recommended with certainty, but with no basis in facts, findings or substantiated outcomes. The 'four Ds' are an example of a universally accepted set of instructions to quit smoking that has little basis in science. This anomaly is at odds with the era of evidence‐based medical interventions and should be addressed.